2022
DOI: 10.3389/fimmu.2022.911919
|View full text |Cite
|
Sign up to set email alerts
|

TIGIT as a Promising Therapeutic Target in Autoimmune Diseases

Abstract: Co-inhibitory receptors (IRs) are molecules that protect host against autoimmune reactions and maintain peripheral self-tolerance, playing an essential role in maintaining immune homeostasis. In view of the substantial clinical progresses of negative immune checkpoint blockade in cancer treatment, the role of IRs in autoimmune diseases is also obvious. Several advances highlighted the substantial impacts of T cell immunoglobulin and ITIM domain (TIGIT), a novel IR, in autoimmunity. Blockade of TIGIT pathway ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 151 publications
0
13
0
Order By: Relevance
“…Next, we found a downregulation of TIGIT in cytotoxic CD57 + CD4 + T cells of children from the ≥ 2 Aab first group. The important role of TIGIT was recently highlighted in the context of autoimmune diseases 27 . The increased expression of immune response negative regulators was shown to limit β cell destruction by autoreactive T cells in a mouse model of type 1 diabetes 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Next, we found a downregulation of TIGIT in cytotoxic CD57 + CD4 + T cells of children from the ≥ 2 Aab first group. The important role of TIGIT was recently highlighted in the context of autoimmune diseases 27 . The increased expression of immune response negative regulators was shown to limit β cell destruction by autoreactive T cells in a mouse model of type 1 diabetes 28 .…”
Section: Discussionmentioning
confidence: 99%
“…S100A12, a member of the small calcium-binding S100 protein family, is secreted primarily by neutrophils, macrophages, and smooth muscle cells; it is released in inflammatory states and functions as a pro-inflammatory molecule and can be used as a diagnostic biomarker for various inflammatory diseases such as rheumatoid ( 22 , 23 ). Co-inhibitory receptor (IR), a recently discovered molecule, protects the host from autoimmune responses and maintains peripheral self-tolerance; in addition, it maintains immune homeostasis, T-cell immunoglobulin, and ITIM structural domains (TIGIT) and plays a crucial role in immune regulation by promoting regulatory T cells ( 24 ). Serpin peptidase inhibitor, clade B (ovalbumin), member 2 (SERPINB2) is often expressed in lymphoid organs such as the spleen and in inflammatory responses or subjected to induced expression under various conditions of infection and pro-inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell immunoreceptor with immunoglobulin and ITIM domain (TIGIT) is highly expressed on Tregs. Research has demonstrated that the interaction of TIGIT with CD155 on human DCs can suppress DC function [39]. T-cell immunoglobulin-3 (TIM-3), a negative regulator of type 1 T helper (Th1) immunity, is expressed by a significant number of tumour-infiltrating lymphocyte (TIL) Tregs.…”
Section: Suppressive Mechanisms Of Tregsmentioning
confidence: 99%